Prácticas de sanación para el afrontamiento COVID-19, durante el Confinamiento. comunidad de Vinchoa. noviembre 2020 – marzo 2021. - Barba Bonilla, Alexandra Estefania (2021)
Purpose: To reveal the healing practices for coping with COVID-19 during confinement in the Vinchoa communities, through an indepth interview to know and understand their cultural practices. Methodology: Ethnographic qualitative approach research whose study population was 30 inhabitants of the communities of Vinchoa Grande, Vinchoa Central, Vinchoa Chaquisca, 10 distributed by each community, of which 6 were women and 4 men. An indepth interview was applied prior to the signing of the informed consent, the 15 questions were grouped into categories: Seeking relief in the pharmacy, my cultural practices, my experiences, what I am learning, fighting the Covid. The Atlas Ti software was used for data tabulation. Results: the traditional healing practices against Covid-19 used by the inhabitants of Vinchoa consists of the use of medicinal plants, such as: eucalyptus, ginger, pumín, rue, lemon verbena, rosemary, cypress, linden, cascarilla, chamomile, in form of hot infusions, baths, steams for disinfection and aromatization of the home, combining with the use of western practices with products such as: alcohol, antiseptic gel; the consumption of drugs: paracetamol, ibuprofen, fluisil, aspirin, azithromycin, vitamin C, complex b, ivermin. Conclusions: the inhabitants of Vinchoa consume medicines with and without a medical prescription, on the recommendation of relatives, neighbors or social networks, in combination with medicinal plants in the form of drinks, steam, baths or disinfectants to avoid contagion and minimize the symptoms of Covid -19, infected relatives of the studied homes have been treated and cared for at home making use of traditional and generational knowledge combining the plants provided by nature and drugs from pharmacies. Keywords: Covid-19, healing practices, Western medicine, ancestral medicine, medicinal plants.